Mapping the communicative ecology of Latin American migrant women in New Zealand - Luciana Nunes Hoffman (Asia Pacific Network, 2019)
This article is based on a study that focused on the narratives of Latin American migrant women (LAMW) in New Zealand and the role formal and informal communication networks play in their migration experiences. These networks were both online and offline and supported by the ethnic media. Informed by a feminist theoretical framework, this qualitative investigation employed the oral history and communicative ecology approaches. This study demonstrated the existing complexity and interrelationship between the communication networks, the feminisation of migration and migrant women’s empowerment.